Upaya Manajer Untuk Meningkatkan Kepuasan Anggota Dalam Memanfaatkan Unit Usaha Toserba Pada Koperasi Inti - Made Winda (Universitas Mahendradatta Denpasar, 2019)
Cooperative is a joint economic power, to jointly face various problems, whether in the field of management, capital, and business fields that exist in the cooperative that if the problem is not quickly find a way out, then the cooperative will be difficult to move forward and compete with other business economic institutions .In an effort to achieve organizational goals, managers are strongly required to master the management of cooperative in this case managers, managers and employees who are trusted by the Meeting Members. They are required to be more capable in running the organization in order to carry out its duties in helping improve the business performance of cooperative.Expectations of satisfaction level of members of Koperasi INTI have been implemented by the manager quite well, although there is a small part of each indicator that is still not fulfilled. This will make reference for managers in improving member's satisfaction in utilizing services in department store business unit. The fact that the service performed in the department store unit is not in accordance with the expectations that the manager wants and not in accordance with the reality in the field. This causes the services undertaken in the department store unit less good, thus causing the lack of utilization of department store business unit.